QSAR Study of N-[3-(1,1,2,2-Tetrafluoroethoxy)benzyl]-N- (3-phenoxyphenyl)trifluoro-3-amino-2-propanol Derivatives as Antiatherogenic Agents - PRATAP SINGH, HEMENDRA; NEMA, R.K.; SINGH, ANOOP; D. GUPTA, SAYAN (Asian Journal of Chemistry, 2010)
Coronary heart disease is one of the dreaded diseases prevailing now a day, which can be treated by the use of more potent and selective agents. One of such agent is Cholesterol ester transfer protein inhibitors. N-[3-(1,1,2,2-tetrafluoroethoxy)benzyl]-N-(3-phenoxyphenyl)- trifluoro-3-amino-2-propanol derivatives has screened as antiatherogenic agents. So, N-[3-(1,1,2,2-tetrafluoroethoxy)benzyl]-N-(3- phenoxyphenyl)trifluoro-3-amino-2-propanol derivatives were selected for quantitative structure activity relationships, for the present study. QSAR studies with significant equations indicate that the molar refractivity in the R3 position of the parent compound negatively contributed for activity.